Audit to Assess the Availability of Electrocardiogram (ECG) Machines on the Inpatient Units at Leeds and York Partnership Foundation Trust (LYPFT) - Sabah Yasin; Abhijit Chakrabarti (BJPsych Open, 2025)
Aims: Establish the scale of the problem by collecting data on how frequently electrocardiogram (ECG) machines are not available, and the time doctors are spending searching for them.